2016
DOI: 10.1038/srep24202
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Fucoidan in β-Tricalcium phosphate-Chitosan scaffold prompts the differentiation of human bone marrow stromal cells into osteogenic lineage

Abstract: In our previous study, we reported the fabrication and characterization of a novel tricalcium phosphatefucoidan-chitosan (TCP-Fu-Ch) biocomposite scaffold. However, the previous report did not show whether the biocomposite scaffold can exhibit osteogenic differentiation of human bone marrow stromal cells in osteogenic media and normal media supplemented with platelet-derived growth factor (PDGF-BB). On day 15, the release of osteocalcin, was significant in the TCP-Fu-Ch scaffold, when compared with that in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 51 publications
(53 reference statements)
0
24
0
Order By: Relevance
“…Fucoidan has important properties for artificial bone development, namely, inducing osteogenic genes and enhancing febrile collagen matrix formation, while chitosan can be used to modify cell adhesion, proliferation, and differentiation. Scaffolds composed of fucoidan and chitosan have been established as biomaterials for bone regeneration [141][142][143][144][145][146]. Likewise, several examples of hydrogels based on fucoidan and chitosan can be found in the literature developed mainly as a solution for wound healing [144,[147][148][149][150].…”
Section: Biomedical Applications Of Fucoidan and Chitosanmentioning
confidence: 99%
“…Fucoidan has important properties for artificial bone development, namely, inducing osteogenic genes and enhancing febrile collagen matrix formation, while chitosan can be used to modify cell adhesion, proliferation, and differentiation. Scaffolds composed of fucoidan and chitosan have been established as biomaterials for bone regeneration [141][142][143][144][145][146]. Likewise, several examples of hydrogels based on fucoidan and chitosan can be found in the literature developed mainly as a solution for wound healing [144,[147][148][149][150].…”
Section: Biomedical Applications Of Fucoidan and Chitosanmentioning
confidence: 99%
“…To examine the level of osteogenic differentiation, gene xpression was employed according to a previously established method. 36…”
Section: Gene Expressionmentioning
confidence: 99%
“…Chitosan and fucoidan are oppositely charged polysaccharides, thus enabling the formation of polyelectrolyte complexes via self-assembly [ 31 , 32 , 33 ]. Several studies have suggested that chitosan–fucoidan polyelectrolyte/nanoparticles have great advantages in drug delivery [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ] and tissue engineering [ 40 , 41 , 42 ] due to their efficient drug encapsulation and cellular uptake.…”
Section: Introductionmentioning
confidence: 99%